Generalized stochastic derivatives on spaces of nonregular generalized functions of Meixner white noise - Kachanovsky, N.A. (Український математичний журнал, 2008)
We introduce and study generalized stochastic derivatives on the Kondratiev-type spaces of nonregular generalized functions of Meixner white noise. Properties of these derivatives are quite analogous to the properties of the stochastic derivatives in the Gaussian analysis. As an example we calculate the generalized stochastic derivative of the solution of some stochastic equation with a Wick-type nonlinearity.